Thrombocytopenia Impairs Host Defense Against Burkholderia pseudomallei (Melioidosis). (11th October 2018) - Birnie, Emma; Claushuis, Theodora A M; Koh, Gavin C K W; Limmathurotsakul, Direk; Day, Nicholas P J; Roelofs, Joris J T H; Ware, Jerry; Hou, Baidong; de Vos, Alex F; van der Poll, Tom; van 't Veer, Cornelis; Wiersinga, W Joost
Abstract : Thrombocytopenia predicts mortality in melioidosis patients and during experimental melioidosis, platelets play a protective role in both innate immunity and vascular integrity. Abstract: Background: Infection with the gram-negative bacillus Burkholderia pseudomallei (melioidosis) is an important cause of pneumosepsis in Southeast Asia and has a mortality of up to 40%. We aimed to assess the role of platelets in the host response against B. pseudomallei infection. Methods: Association between platelet counts and mortality was determined in 1160 patients with culture-proven melioidosis. Mice treated with (low- or high-dose) platelet-depleting antibody were inoculated intranasally with B. pseudomallei and killed. Additional studies using functional glycoprotein Ibα–deficient mice were conducted. Results: Thrombocytopenia was present in 31% of patients at admission and predicted mortality in melioidosis patients even after adjustment for confounders. In our murine-melioidosis model, platelet counts decreased, and mice treated with a platelet-depleting antibody showed enhanced mortality and higher bacterial loads compared to mice with normal platelet counts. Low platelet counts had a modest impact on early-pulmonary neutrophil influx. Reminiscent of their role in hemostasis, platelet depletion impaired vascular integrity, resulting in early lung bleeding. Glycoprotein Ibα–deficient mice had reduced platelet counts during B. pseudomallei infection together with an impaired local host defense in the lung. Conclusions: Thrombocytopenia predicts mortality in melioidosis patients and, during experimental melioidosis, platelets play a protective role in both innate immunity and vascular integrity.